PKM PENDAMPINGAN DIGITALISASI SEKOLAH SMPIT AJIMUTU GLOBAL INSANI TAMBUN UTARA-BEKASI BERBASIS ARTIFICIAL INTELLIGENCE - Saryoko, Andi; Aziz, Faruq; Elyana, Instianti; Rizky, Mhd; Junior, Mario Christian (Jurnal AbdiMas Nusa Mandiri, 2025)
Digital transformation in education is inevitable; however, many schools such as SMPIT Ajimutu Global Insani still face challenges in adopting technology. The main issue lies in the manual learning evaluation process, which leads to teacher time inefficiency and limited question variation, ultimately affecting learning quality. This community service program aims to bridge the digital gap by implementing an Artificial Intelligence (AI)-based solution. The novelty of this initiative lies in the use of the Question Maker Application (QUMAA)—an innovative tool that automates question generation and includes a question difficulty analysis feature, offering a comprehensive approach to digitizing school evaluation systems. The program was carried out through a participatory method consisting of five stages: needs assessment, application development, intensive training and mentoring for teachers, implementation and evaluation, as well as monitoring and sustainability planning. The results showed that the learning evaluation process was successfully digitized, with teachers’ ability to understand and use AI increasing by more than 50%, and question preparation time reduced by up to 50%. This program not only facilitated technology transfer but also empowered teachers and strengthened the school institution. The implementation of the AI-based QUMAA proved effective in improving efficiency and quality in learning evaluation. Furthermore, this model can be replicated in other schools as a concrete contribution to achieving the SDGs in education, emphasizing the need for ongoing support and funding to sustain digital innovation in the education sector.